Reconstructing Islamic Identity in Modern Times: A Narrative Review of Educational Reform and Intellectual Responses - Rahman, Gohar (Sinergi International Journal of Islamic Studies, 2025)
This study offers a comprehensive narrative review of the evolving relationship between Islamic philosophy and Western modernity. It aims to explore how Muslim intellectuals respond to the challenges of modern epistemology and secularism by reinterpreting classical Islamic concepts. The review applies a structured methodology involving major academic databases such as Scopus, PubMed, and Google Scholar, employing keywords like "Islamic philosophy," "modernity," and "identity formation." Articles were selected based on peer-reviewed credibility, conceptual relevance, and thematic alignment with the focus on philosophical responses to modernity. Findings reveal that while dominant narratives portray Islam and modernity as dichotomous, contemporary scholars propose integrative models, such as Taha Abderrahman's trusteeship paradigm and reinterpretations of tawḥīd, ʿ aql, and fanā’. These concepts are adapted to address the ethical and epistemological crises brought on by secularism and postcolonial identity fragmentation. The discussion also identifies colonialism, global modernism, and identity crises as systemic barriers that shape the discourse. In response, scholars emphasize educational reform, legal reinterpretation, interfaith and inter-disciplinary dialogue, and the revitalization of traditional epistemologies as critical interventions. This study concludes that dynamic engagement with modernity through the lens of Islamic tradition can foster inclusive intellectual frameworks and social cohesion. It recommends further research on the implementation and impact of these reformist strategies, highlighting the value of integrating classical Islamic values into modern academic and sociopolitical structures.